Possibilities for natural regeneration of scots pine woods and establishing a long-term trial in Őrség National Park (Western Hungary) - Bodonczi, László (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
Experimental studies conducted in Scots pine (Pinus sylvestris) woods in the Őrség National Park are reported in this paper. Based on the common occurrence of natural Scots pine regeneration in the area and on earlier relevant literature, the author is convinced that there must be other, more natural ways of forest regeneration for Scots pine woods than the currently practiced clearcutting. In the Őrség National Park this management is applied even in strictly protected areas, although relevant literature (Temesi 1997, Borhidi és Sántha 1999, Bartha 2001) and nature conservation laws prohibit it. Due to its negative impacts, the area of clearcuts should be radically decreased in the future, although reduction in the volume of wood production is not an aim. Our purpose was to set up an experiment on Scots pine wood management that – on the long run – may contribute to a marked decline of the practice of clearcutting by elaborating alternative, more natural methods for forest regeneration even for profit oriented forest management.